Peran Kompensasi dan E-Recruitment: Analisis Minat Melamar Pekerjaan Pada Calon Karyawan/Pegawai Generasi Millenial - Shalahuddin Shalahuddin; Meilia Fatika Sari; Nurul Hidayat (Islamic University of Kalimantan MAB Banjarmasin, 2022)
The purpose of this study is to find out whether compensation and e- recruitment can attract prospective millennial employees to work and whether the use of the internet which has become a millennial lifestyle can help them find the job they want. The hypothesis in this study is that compensation has a positive effect on interest applying for a job and e-recruitment has a positive effect on interest in applying for a job. In this study using a quantitative approach to survey method. Sampling technique that is using purposive sampling, the respondents in this study were alumni of the Borneo Tarakan University totaling 225 people from the management and economic development majors. Then analyzed using spss that is t test. The result of this study indicate that compensation has a positive effect on interest in applying for a job and e-recruitment also has a positive effect on interest in applying for a job.